Teachers' frequency of assessment, classroom management and instructional delivery as predictors of students’ academic achievement in english language and mathematics at SSS 2 in Lagos state (2014)
This study examined the influence of teachers’ frequency of assessment, classroom management and instructional delivery on secondary school two students’ academic achievement in English Language and Mathematics. Three hundred (300) students and (24) teachers were randomly selected for the study in three educational district, six local government areas and twelve secondary schools of Lagos state. Mathematics Teachers Observation Rating Scale (MTORS) of 35 items with reliability coefficient of 0.78 was administered on selected twelve SSII Mathematics teachers and twelve English teachers while the students Mathematics and English Language Test was administered to selected 300 students of SSS II. The data collected were analyzed using multiple regression analysis at significant level of 0.05.The inter-correlation matrix showed that there is no multi-collinearity among the predictor variables. The results showed that teachers instructional delivery, frequency of assessment and classroom management on students achievement in English language are significant (β - 0.221, t(299) - 3.870,p<0.05), (β - -0.298,1(299) - -3.304, p <0.05) and (β - -0.901,1(299) - -2.853, p <0.05). Also, instructional delivery, frequency of assessment and classroom management on students achievement in Mathematics are significant (β - -0.182,1(299) - 4.792,p<0.05), (β = -0.298, 1(299) = -3.304, p <0.05), (β = 1.919, t(299) = 4.946, p <0.05). It was recommended that teachers should bike into consideration the instructional delivery methods they use that best suit their students’ achievement especially in Mathematics and English Language for the purpose of improving their academic achievement. Frequency of assessment by teachers should be inculcated by other teachers that have not been making it their style to assess students at least once a day after each lesson to improve the quality of education. Teachers should also place more importance on management of their classroom to make sure that almost all the students in the classroom are participating.